Assessment of sustainability of lobster fisheries in Dampar Beach, Lumajang Regency, East Java, Indonesia - Mahmud, Amar; Munir, Misbakhul; Maisaroh, Dian Sari (Journal of Marine Resources and Coastal Management, 2022)
Dampar Beach is one of the area in Lumajang which has abundant fisheries resources and lobster is one of export commodities. Nowadays, increased trade and local market demand led to an increase in lobster sales and will lead to a decrease in lobster stocks. Therefore, a sustainability analysis is needed in managing these fishery resources. This study aims to determine the level of sustainability of lobster fisheries in Dampar Beach, Lumajang in four dimensions, i.e. economic, social, ecological, and technological dimension. The sustainable management strategy of lobster fisheries also determined and discussed. The research method for the analysis of sustainability status uses RAPFISH (Rapid Appraisal for Fisheries Sustainability). This type of research uses a descriptive method with a quantitative approach. The results showed that the sustainability index value of the economic and technology dimension are 39.29% and 48.79%, respectively (less sustainable). The social and ecological dimension are 60.44% and 50.72%, respectively (enough sustainable). The strategies for lobster fisheries at Dampar Beach, Lumajang should focus more on attributes that have high leverage, especially on the social, economy, and ecology dimensions. The utilization of lobster resources in a sustainable manner is basically the goal of management which guarantees the level of resource utilization that does not damage or exceed its recovery capacity, so that it can serving the living needs of present and future generations.